Productivity of sorghum and millets under different in-field rainwater management options on soils of varying fertility status in Zimbabwe - Makuchete, Layton; Hove, Apollonia; Nezomba, Hatirarami; Rurinda, Jairos; Mbanyele, Vengai; Mlambo, Shaw; Nyakudya, Elijah; Mtambanengwe, Florence; Mapfumo, Paul (Frontiers in Agronomy, 2024)
Traditional cereal crops are important for food and nutrition security in rural communities of southern Africa, but their productivity is often constrained by low soil water largely linked to low seasonal rainfall and long intra-seasonal dry spells. Planting basins (PB), tied ridges (TR), and conventional ploughing (CP) were evaluated, over two cropping seasons (2020/2021 and 2021/2022), for their effects on sorghum [Sorghum bicolor (L.), Moench], pearl millet [Pennisetum glaucum (L.) R.Br.], and finger millet [Eleusine coracana (L.) Gaertn] productivity on degraded (<0.4% soil organic carbon) and productive (>0.6% soil organic carbon) fields under rainfed conditions in Mbire (<450 mm rainfall year−1) and Mutasa (>800 mm rainfall year−1) districts in Zimbabwe. Field trials were established on degraded and productive field sites in each district, with sorghum, pearl millet, and finger millet either sown as monocrops or intercropped with cowpea. The experiments were laid out in a 2 × 3 × 3 factorial in a randomized complete block design (RCBD). The highest sorghum grain yield response of 2100 kg ha−1 was attained under PB on productive soils. Overall, PB and TR increased sorghum, finger millet, and pearl millet grain yields by 43% to 58% compared with CP. Growing sorghum, finger millet, and pearl millet on productive soils increased grain yields by 64%, 33%, and 43%, respectively, compared with degraded soils. Intercropping sorghum, pearl millet, and finger millet with cowpea increased cereal yields by between 23% and 42% over the sole crops. Rainwater use efficiency averaged 1 kg grain mm−1 on productive fields and 0.4 kg grain mm−1 on degraded fields. PB produced the highest net profit of $US408 on a productive field. Overall, production of sorghum and millets on productive soils gave positive economic returns irrespective of rainwater management option and cropping system. Conversely, 63% of the treatments on degraded soils recorded negative economic returns in both districts. We conclude that in-field rainwater management technologies combined with other agronomic practices like intercropping increase the productivity of sorghum and millets under rainfed conditions. However, degraded soils remain a challenge for the increased productivity of traditional cereal crops.